Apologetika Presuposisi Triperspektivalisme Cornelius Van Til Terhadap Agnostisisme - Kalis Stevanus; Ivo Arbie Mauclau (SANCTUM DOMINE: JURNAL TEOLOGI, 2021)
In the midst of the spread of agnostic thingking, it posess a serious threat to religious communities, including the Christian faith. This article aims to provide an understanding for Christian practitioners so that they can be responsible for their faith towards agnostic thinking, who became human in the preson of Jesus gives us the understanding that God shows His presence in human life. This article was compiled using the literature study method by looking at the phenomena that occur, so that from each of these discussions it will provide a conclusion that God who is understood transcendetally can also be experinced immanently.